2019
DOI: 10.1080/21691401.2019.1594862
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles from Scutellaria barbata and its anticancer activity in pancreatic cancer cell (PANC‐1)

Abstract: Nanotechnology has been materialized as a proficient technology for the development of anticancer nanoparticles all the way through an environment-friendly approach. Conventionally, nanoparticles have been assembled by dissimilar methods, but regrettably rely on the negative impact on the natural environment. Amalgamation of nanoparticles by means of plant extract is alternate conservative methods. Scutellaria barbata species was used majorly as food or as medicines against various diseases, and extensive rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…More so, due to the large surface area of nanomaterials, they can be employed as site directed targeted therapy in cancer when functionalized or conjugated with peptides, antibodies, DNA or RNA strands, aptamers and other small molecules ( Figure 2 ). The site directed targeted therapy concept has been an effective approach in cancer treatment due to the presence of several molecular receptors located on the surface of the endothelial layer of the tumour cells which aids the endothelial cell adhesion molecule-mediated targeted drug delivery process [ 56 , 57 ]. Nanotechnology has also offered an alternative approach in circumventing multidrug resistance due to the capacity of nanoparticulate systems to by-pass the drug efflux mechanism [ 50 , 51 ].…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More so, due to the large surface area of nanomaterials, they can be employed as site directed targeted therapy in cancer when functionalized or conjugated with peptides, antibodies, DNA or RNA strands, aptamers and other small molecules ( Figure 2 ). The site directed targeted therapy concept has been an effective approach in cancer treatment due to the presence of several molecular receptors located on the surface of the endothelial layer of the tumour cells which aids the endothelial cell adhesion molecule-mediated targeted drug delivery process [ 56 , 57 ]. Nanotechnology has also offered an alternative approach in circumventing multidrug resistance due to the capacity of nanoparticulate systems to by-pass the drug efflux mechanism [ 50 , 51 ].…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
“…In their study, it was shown that the successful engineering of the herceptin-loaded micellar nanocarriers can deliver more drugs selectively into the cancer cells, and killed them more efficiently, as well as displayed longer blood half-life than the native drug. Other studies which have employed green synthesis of NPs in cancer treatment include the anticancer activity of green synthesised gold NPs from Scutellaria barbata on pancreatic cancer cell (PANC-1) [ 56 ]. The anticancer potential and photodynamic therapy of green synthesized silver NPs from Cynara scolymus leaf extracts on breast cancer cells [ 69 ], and the green synthesis of anisotropic gold NPs from cocoa aqueous extracts for cancer photothermal therapy [ 70 ].…”
Section: Nanotechnology In Cancer Treatmentmentioning
confidence: 99%
“…The temperature of Gold (III) chloride trihydrate solution in Ostruthin was increased from 30 to 70 o C with multiple of 10 o C for every temperature reading. The changes in the colour of the solution observed at (5,10,20,30, and 60 min) of every reaction time.…”
Section: The Green Synthesis Of the Aunpsmentioning
confidence: 99%
“…There are many applications in the biomedical field as antimicrobial activities, stabilizing with proteins, and peptides [4]. The synthesis of AuNPs can perform on using green route methods according to their cytotoxicity and electrochemical activity [5][6][7][8], inflammation [9], and antimicrobial activities [10]. Many articles have been reported to synthesize gold and silver nano from extracted plants and gold and silver ions and apply in medical chemistry [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…SB has long been used in TCM to treat bacterial infections, hepatitis, and tumors along with other herbs (Zhang et al, 2017). SB extract was reported to have anticancer activities in many tumor cell lines, including breast cancer, colorectal cancer, and hepatocarcinoma (Tao and Balunas, 2016;Liu et al, 2018;Wang et al, 2019). SB extract treatment significantly suppressed the activation of several colorectal cancer-related pathways, including STAT3, Erk, and p38 signalings in tumor tissues, and altered the expression of multiple critical target genes such as Bcl-2, Bax, cyclin D1, CDK4, and p21 (Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%